If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 14 = 3x + -31 Reorder the terms: 14 + 2x = 3x + -31 Reorder the terms: 14 + 2x = -31 + 3x Solving 14 + 2x = -31 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 14 + 2x + -3x = -31 + 3x + -3x Combine like terms: 2x + -3x = -1x 14 + -1x = -31 + 3x + -3x Combine like terms: 3x + -3x = 0 14 + -1x = -31 + 0 14 + -1x = -31 Add '-14' to each side of the equation. 14 + -14 + -1x = -31 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = -31 + -14 -1x = -31 + -14 Combine like terms: -31 + -14 = -45 -1x = -45 Divide each side by '-1'. x = 45 Simplifying x = 45
| 9r-9=-342 | | 4/3x-10=24 | | 7k-8(10)=45 | | -4=-9+v | | 4b-7=101 | | 45(n+6)=35n | | 2.56=x/2 | | -7=w+8 | | 2p+7=-53 | | (Y/6)4 | | 4x+1x+25+3x-5=2y-12 | | 8(9)+7a=79 | | 4c+6=-130 | | 5x-26=3x+20 | | 3+2(x+2)=9+3x | | (Y/-15)5 | | -8(x-2)=24 | | 16x^4-8x^2=0 | | -4x^2+5x=y | | =.59=x/4-0.09 | | 17(x+6)=306 | | 8i(9-4I)= | | 6.5=-4(-n-4) | | 3*(2x+2)=4*(x+8) | | 14x+2=16+7x | | 2x+13=35-10x | | 2x+.3=.2x+2.1 | | 2x^4-6x^5=12x^2-36x | | 5x-13+11x-61+7x-29=180 | | 64+4x=-1 | | 7=11m-5m | | 4x-x+3=5x+8 |